Is this the beginning of the end for retail websites? A professional perspective - Ramos, R. (2021)
This paper expects to understand professionals opinion concerning the impact of the increasing use of Social Media (SM) and commercial Mobile Applications (MA) instead of retail websites in their online strategy. Unstructured interviews with Internet professionals were applied on the LinkedIn professional SM platform, and one hundred and twenty-seven professionals provided their perspective. Data were analyzed using a Text Mining approach, and the outcome revealed professionals resistance to set SM in the center of the online strategy and highlighted the preference of users to use search engines that, in turn, will lead them to a retail website.